THE INFLUENCE OF GENDER DIFFERENCES OF COMPANY EXECUTIVES IN INDONESIA AGAINST THE RISK OF FALLING STOCK PRICES - Stefany Shannova; Valentino Budhidharma (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
The purpose of this study is to determine the influence of gender differences between men and women on the risk of falling company stock prices in Indonesia. The study also wants to see if female executives have a positive or negative influence on the risk of falling stock prices. This study has an observation in which there are 433 companies listed on the Indonesia Stock Exchange from 2010 to 2019 with certain criteria. There are 2 models used in this study, namely the Logit Model, and the Generalized Method of Moments (GMM). The results showed that female executives did not have a significant influence on the risk of falling company stock prices. In addition, the position of the CFO compared to the CEO also does not have a significant positive influence in influencing the risk of falling stock prices.